Genetic and phenotypic correlations among feed efficiency, immune and production traits in indigenous chicken of Kenya - Miyumo, Sophie A.; Wasike, Chrilukovian B.; Ilatsia, Evans D.; Bennewitz, Jorn; Chagunda, Mizeck G. G. (Frontiers in Genetics, 2023)
This study estimated genetic and phenotypic relationships among feed efficiency, immune and production traits measured pre- (nine to 20 weeks of age) and post- (12 weeks from on-set of lay) maturity. Production traits were average daily gain (ADG) and average daily feed-intake (ADFI1) in the pre-maturity period and age at first egg (AFE), average daily feed-intake (ADFI2) and average daily egg mass (EM) in the post-maturity period. Feed efficiency comprised of residual feed intake (RFI) estimated in both periods. Natural antibodies binding to keyhole limpet hemocyanin (KLH-IgM) and specific antibodies binding to Newcastle disease virus (NDV-IgG) measured at 16 and 28 weeks of age represented immune traits pre- and post-maturity, respectively. In the growing period, 1,820 records on ADG, KLH-IgM and NDV-IgG, and 1,559 records on ADFI1 and RFI were available for analyses. In the laying period, 1,340 records on AFE, EM, KLH-IgM and NDV-IgG, and 1,288 records on ADFI2 and RFI were used in the analyses. Bi-variate animal mixed model was fitted to estimate (co)variance components, heritability and correlations among the traits. During the growing period, moderate to high heritability (0.36 – 0.68) was estimated for the production traits and RFI while the antibody traits had low (0.10 – 0.22) heritability estimates. Post-maturity, the production traits and RFI were moderately (0.30 – 0.37) heritable while moderate to high (0.25 – 0.41) heritability was estimated for the antibody traits. Genetic correlations between feed efficiency and production traits in both periods showed that RFI had negative genetic correlations with ADG (-0.47) and EM (-0.56) but was positively correlated with ADFI1 (0.60), ADFI2 (0.74) and AFE (0.35). Among immune and production traits, KLH-IgM and NDV-IgG had negative genetic correlations with ADG (-0.22; -0.56), AFE (-0.39; -0.42) and EM (-0.35; -0.16) but were positively correlated with ADFI1 (0.41; 0.34) and ADFI2 (0.47; 0.52). Genetic correlations between RFI with KLH-IgM (0.62; 0.33) and NDV-IgG (0.58; 0.50) were positive. Feed intake, RFI and antibody traits were positively correlated with estimates ranging from 0.48 to 0.82. Results indicate selection possibilities to improve production, feed efficiency and immune-competence in indigenous chicken.